Determination of Lead in Waste Water Using Cyclic Voltammetry by Platinum Wire Electrode - Riyanto Riyanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2014)
Determination of lead in waste water using cyclic voltammetry by platinum wire electrode has been carried out. The cyclic voltammetry method was performed in a three electrodes system using platinum wire as a working electrode, an Ag/AgCl (saturated KCl) as reference electrode and platinum plate as the counter electrode. PGSTAT 100 N 100 V/250 mA type (Metrohm Autolab) was used for electroanalysis measurements. Electroanalysis of lead in waste water was performed in 0.1 M KClas an electrolyte. From this research showed that the developed electroanalysis lead in waste water using platinum wire electrode are accurate, precise, reproducible and inexpensive with acceptable correlation of determination (R2 = 0.999), LOD = 0.9029 mg/L , LOQ = 3.0098 mg/L and recovery = 100,67%. The methods can be used for the analysis of lead in waste water. This method is simplicity of sample preparation and use of low cost reagents are the additional benefit.